Rediscovery of the genus Atyopsis Chace, 1983 (Decapoda: Atyidae) in mainland India following a 72-year gap - Kunjulakshmi, Kozhikkaparambil; Santos, Maclean Antony; Prakash, Sanjeevi (Zootaxa, 2025)
This study resolves a longstanding uncertainty surrounding the presence of the genus Atyopsis from mainland India, based on recent collections from the Mulki (Karnataka) and Bhubaneswar (Odisha) regions of western and eastern India. Originally reported 72 years ago as Atya moluccensis by Tiwari (1951), the report lacks morphological validation. This combined with absence in subsequent records has led to scepticism regarding the genuine occurrence of the genus in India’s mainland freshwater ecosystems. In the present study, we report on the rediscovery of Atyopsis, and identified the species as Atyopsis spinipes, thereby reaffirming and validating the presence of the genus after seven decades. Atyopsis spinipes can be easily distinguished from its congener A. moluccensis, based on the shape and armature of the rostrum and the proportions of the endopod of first pleopod in males. This finding underscores the need for continued systematic surveys to shed light on the understudied shrimp fauna of India’s freshwater ecosystems.